2013
DOI: 10.3390/foods2030364
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Kinetics of Various Pathogenic E. coli on Fresh Perilla Leaf

Abstract: Growth kinetics for Escherichia coli O157:H7 in perilla leaves were compared to those of pathogenic E. coli strains, including enteropathogenic (EPEC), enterotoxigenic (ETEC), enteroinvasive (EIEC) and other enterohemorrhagic (EHEC) at 13, 17, 24, 30 and 36 °C. Models for lag time (LT), specific growth rate (SGR) and maximum population density (MPD) as a function of temperature were developed. The performance of the models was quantified using the ratio method and an acceptable prediction zone method. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Additional information on the proximate composition of the vegetables and fruits under investigation are shown in Table 2 . These values are comparable to those reported by Kim et al, 34 for perilla leaves inoculated with E. coli O157:H7 at 36 °C (LPD = 2.40 ± 0.32 h; EGR = 0.55 ± 0.11 CFU/mL/h). The growth of the E. coli O157:H7 strain on the epicarp of the vegetables and fruits was slower than that observed under controlled laboratory conditions.…”
Section: Resultssupporting
confidence: 90%
“…Additional information on the proximate composition of the vegetables and fruits under investigation are shown in Table 2 . These values are comparable to those reported by Kim et al, 34 for perilla leaves inoculated with E. coli O157:H7 at 36 °C (LPD = 2.40 ± 0.32 h; EGR = 0.55 ± 0.11 CFU/mL/h). The growth of the E. coli O157:H7 strain on the epicarp of the vegetables and fruits was slower than that observed under controlled laboratory conditions.…”
Section: Resultssupporting
confidence: 90%
“…The predicted SGR and LT values for generic E. coli in Garaetteok were determined to be 0.198 h -1 and 10.025 h at a storage temperature of 18°C (Table 3). A marked increase ([ 3-fold) and decrease ([ twofold) in the SGR and LT values, respectively, were observed for the E. coli in Garaetteok in this study compared with a study reported by Kim et al (2013), who used similar storage temperatures for predictions: the predicted SGR and LT values for E. coli O157:H7 were found to be 0.055 h -1 and 20.40 h on fresh Perilla leaf at a storage temperature of 17°C. This difference may be due to the different substrates and different strains of E. coli used in these studies.…”
Section: Predictive Model Development In Garaetteoksupporting
confidence: 67%
“…Differences in growth kinetics have been reported among strains of foodborne pathogens such as E . coli [ 51 ]. Similarly, the differences in the growth rate obtained in the present work and those reported by Young et al [ 25 ] may be attributed to strain biological variability.…”
Section: Discussionmentioning
confidence: 99%